2014
DOI: 10.1021/jp501207y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Block Copolymer Compatibilizers on the Morphologies of Semiflexible Polymer/Solvent Blends

Abstract: We study the influence of block copolymer (BCP) compatibilizers on the domain and interfacial characteristics of the equilibrium morphological structures of semiflexible polymer/solvent blends. Our study is motivated by the question of whether block copolymer compatibilizers can be used to influence the phase separation morphologies resulting in conjugated polymer/fullerene blends. Toward this objective, we use a single chain in mean field Monte Carlo simulations for the phase behavior of semiflexible polymer/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 76 publications
(125 reference statements)
0
28
0
Order By: Relevance
“…23 Recently, several CG models of P3HT:fullerene system have been developed for studying BHJ morphology evolution with system size compatible with experiments. 25,26 In addition to deterministic MD simulations, stochastic Monte Carlo (MC) is another powerful method to investigate the BHJ morphology at/close to equilibrium in solution, 27,28 which could hold the key toward studying longterm morphology evolution. However, all of these aforementioned computational studies focused on the BHJ morphologies in the bulk; that is, the top and bottom electrodes were not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…23 Recently, several CG models of P3HT:fullerene system have been developed for studying BHJ morphology evolution with system size compatible with experiments. 25,26 In addition to deterministic MD simulations, stochastic Monte Carlo (MC) is another powerful method to investigate the BHJ morphology at/close to equilibrium in solution, 27,28 which could hold the key toward studying longterm morphology evolution. However, all of these aforementioned computational studies focused on the BHJ morphologies in the bulk; that is, the top and bottom electrodes were not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…As a coarsegrained model of the system under consideration, we consider a mixture of homopolymer B, BCP A-B, and explicit solvent S. We use a combination of random phase approximation (RPA) and single chain in mean field (SCMF) simulations to effect the objectives discussed in the preceding section. Many details of our framework are identical to those presented in the context of our previous work, 29 and, hence, we provide only the most pertinent details of the model here.…”
Section: Full Papermentioning
confidence: 99%
“…[30][31][32][33] Liquid crystalline ordering and polymer crystallization are common morphological features that impact the electronic properties and device performance of OSCs. In our previous works, 23,29 we utilized a morphology model that incorporates orientational interac-tions between semiflexible polymers to identify the influence of such features on the morphologies formed by our system of interest. We found that the influence of the polymer semiflexibility is primarily on the qualitative characteristics of the morphology, whereas the phase behavior is affected only to a limited degree.…”
Section: Full Papermentioning
confidence: 99%
“…22,23 Although the popularity of hybrid models in modelling Soft Matter is increasing, [12][13][14]24 their potential in modelling polymer solutions has not yet been fully explored. Currently, hybrid models of polymer solutions 22,23,[25][26][27][28][29][30][31][32][33][34] are build on functionals which are polynomials of local densities of different compounds. Most studies focus on phenomena in the liquid phase (such as self-assembly) and retain only second-order terms, which are equivalent to simple Flory-Huggins interactions.…”
Section: Introductionmentioning
confidence: 99%